World Cup finals: forecasts for biathlon relays using quantum energy diagnostics - Sivakov, V. I.; Saraykin, D. A.; Pavlova, V. I.; Kamskova, Yu. G.; Orekhova, I. L. (Theory and Practice of Physical Culture, 2020)
Quantum energy diagnostics tools for the Russian biathlon team competitive performance forecasts may be effectively applied in the competitive performance planning. Quantum diagnostics driven forecasting method may be applied to select the best competitors to the women's relay team. Objective of the study was to analyze benefits of the express quantum diagnostics-driven competitive performance forecasting method in application to the women's biathlon relay team in the World Cup finals. The quantum diagnostics-driven competitive performance forecasts may heavily contribute to the competitive progress due to the reliable quantum diagnostics functionality rates generated by the new method. The quantum diagnostics method may be described as the contact or remote influence on the body energy system for the performance and functionality recovery process rating purposes in the training, precompetitive and competitive processes. The study tested the biathlon competitors with the low and medium-levels energy coloring profiles indicative of the relevant low and medium fitness levels. Analysis of the energy coloring profiles by the relay stages shows the first stage dominated by the red-greenish, second by the pink-grey, third by pink-reddish and the fourth by light red colors, with the energy mostly presentable in a square (screen) form rather than a circular one - that may be interpreted as indicative of fatigue, over-fatigue and poor adaptability of the bodily systems to competitive stress.